The performance evaluation of PPK and PPP-based Loosely Coupled integration in wooded and urban areas - Gurturk, Mert; Ilci, Veli (UNIV NACIONAL DE COLOMBIA, 2022)
In this study, the authors conducted a series of test measurements in wooded and urban areas and analyzed the results for three main objectives. The first objective is to compare the execution of the Loosely Coupled (LC) and satellite-based solutions in terms of accuracy. Compared to satellite-based solutions, the findings confirmed that the LC-based solutions enhanced accuracy by 1 cm in position and 6-7 cm in height components in the wooded area. In the urban area, LC-based solutions improved the position and height accuracies up to 6 cm and 44 cm, respectively. Also, LC-based solutions bridged the gaps and created a seamless solution in which the gaps reach almost 30% in the urban area trajectory. Secondly, the authors investigated the performance of the GPS-based and GNSS-based solutions. In the wooded area, the GNSS-based solution delivered 2 cm better accuracy in both position and height components than the GPS-based solution. In the urban area, the GNSS-based solution improved the accuracies up to 8 and 36 cm in position and height components, respectively. Also, the solution availability of the GNSS-based process is 10% better than the GPS-based solution. The third objective of this study is to test the performance of the PPP and PPK-based solutions in the two test areas. PPK-based solutions outperformed only 2 cm in position and height components compared to the PPP-based in the wooded area; however, in the urban area, the PPK-based solution improved the accuracies 4-5 dm and 1.1-1.5 meter level in position and height components, respectively. These results indicate that the PPP-based solutions offer a similar level of accuracy to the PPK-based solutions in the wooded area where the satellite visibility is high throughout the trajectory. However, the PPK-based solution provided better positioning accuracies in the urban environment with limited satellite visibility.
Keywords: GNSS; IMU; Loosely Coupled Integration; PPP; PPK; REAL-TIME; ACCURACY; GPS; GPS/GLONASS; NAVIGATION; SYSTEM; SERVICES; GLONASS; IMUS; MAP; Geology